Protecting essential information about genetic variants as trade secrets: a problem for public policy?. Issue 3 (17th May 2019) - Juergens, Alexis K; Francis, Leslie P
ABSTRACT: In 2013, the U.S. Supreme Court held that naturally occurring human genes are not patentable subject matter. This decision, invalidating patents held by Myriad Genetics involving genes affecting breast cancer, appeared to further the constitutional policy behind intellectual property protection to promote scientific progress and to make genetic testing more readily available to patients. However, the decision's ironic aftermath is continuing assertion by genetic testing companies of trade secrets protections over information about the significance of genetic variants. This article analyzes possible approaches to the assertion of trade secret protections over information about the significance of genetic variants. Specifically, we consider five approaches: voluntary responses from the scientific community; Food and Drug Administration (FDA) or CMS regulation; creation of additional march-in rights as under the Bayh Dole Act; compulsory licensing as under patent law; and creation of a public policy exception to trade secret protection. We explore what each approach would require legally if applied to break trade secret barriers, together with their advantages and disadvantages. While our analysis concerns genetic information, we conclude with some thoughts about its relevance to other types of big data now protected by trade secrets such as information about innovations in quality of care.